2016
DOI: 10.1515/pjs-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Appendicitis in Geriatric Patients – Literature Review

Abstract: Demographic changes associated with the aging population mean that surgeons increasingly have contact and make decisions about treating patients from the oldest age groups. the aim of the study was to review the literature concerning the treatment of acute appendicitis in patients over the age of 60 years old. material and methods. A review of the literature published in the years 2000-2015 has been carried out using the PubMed database. The initial number of results corresponding to the query in English, "app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…[6] Previous studies have confirmed that the laparoscopic approach for appendectomies is beneficial for the elderly. [7] For the minimally invasive approach it is typically associated with faster recovery and a shorter hospital stay comparing to open access and can be performed even in ambulatory setting. [810] Registry studies underline the reduction in overall morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Previous studies have confirmed that the laparoscopic approach for appendectomies is beneficial for the elderly. [7] For the minimally invasive approach it is typically associated with faster recovery and a shorter hospital stay comparing to open access and can be performed even in ambulatory setting. [810] Registry studies underline the reduction in overall morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Yaşlı nüfusda sık görülmemekle birlikte, bu hastalarda yandaş hastalıklara bağlı olarak, komplikasyon riski artmaktadır (4). Son çalışmalarda, akut apandisit tanılı yaşlı hastalarda laparoskopik apendektomi daha çok tercih edilmektedir (5,6). Bu çalışmada, 65 yaş ve üzeri akut apandisit nedeniyle ameliyat edilen hastaların değerlendirilmesi amaçlandı.…”
Section: Introductionunclassified